Virtual Reality in Education: A Transformative Tool for Enhanced Learning - Pranav Pathak; Navtej Bhatt (International Journal of Mobile Computing Technology, 2024)
Virtual reality (VR) is a revolutionary technology in education, providing immersive and interactive experiences that can transform the learning process and enhance student engagement with educational content. This review paper provides an in-depth analysis of the applications of VR in education, exploring its effectiveness in enhancing learning outcomes, student engagement, and critical thinking skills. Additionally, the paper delves into the challenges and opportunities associated with integrating VR technology into educational settings, addressing issues such as accessibility, cost, and the need for appropriate content development. By examining current research and case studies, this paper aims to provide a comprehensive understanding of the impact of VR on education and the potential future developments in this field.
Keywords: Accessibility; Virtual reality (VR); education; learning outcomes; student engagement